تطبیق نماذج ونظریات سلوکیات البحث عن المعلومات فى الأطروحات الجامعیة العربیة فى مجالات استخدام المعلومات والافادة منها : دراسة تحلیلیة - د. هانم عبد الرحیم ابراهیم (المجلة الدولية لعلوم المكتبات والمعلومات)
This study has two parts, the first one is an overview of the information seeking behavior: theories and models, including its’ definition, types, and development. It also compares between them to indicate their various features. The second part deals with the analysis of the methods and tools used in the preparation of a sample of Arabic theses in the areas information use and services that have been approved at the University of Alexandria. This study tracks the citation patterns in these and the possibility of the application of theories and models of information behavior to search for information in the Arab community, to open the door for emerging studies to complete the research in this area and develop an Arabic Model for information seeking behavior of Arab societies.